Pengelolaan Model Pembinaan Tahfiz Alqur’an di SMPN 1 Kecamatan Payakumbuh - Wandi Putra; Suswati Hendriani (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2023)
Management of the Al-Qur'an Tahfizd Development Model in Public Schools, the purpose of this research data analysis is to analyze the management of the Al-Qur'an Tahfizd development model at SMPN 1 Payakumbuh District. Data collection methods were carried out through observation, interviews, and documentation. To analyze the data, the authors used a qualitative descriptive analysis technique, and the data testing technique used the triangulation method. The results of the study revealed that the application of the tahfizd Al-Qur'an coaching model with the talqin model in memorizing the Al-Qur'an at SMPN 1 Payakumbuh District begins with reading the verses of the Al-Qur'an, then proceed with repeating the verses. Supporting factors in the Al-Qur'an tahfizd activities at SMPN 1 Payakumbuh District this activity is directly supported by the school principal, students are very enthusiastic in participating in the tahfizd Al-Qur'an program at the end of the semester a tahfizd graduation is held, which motivates students to be more active in memorizing Al-Qur'an. The inhibiting factor in this school is that there are still students who are not fluent in reading the Qur'an, this is due to a lack of cooperation between the homeroom teacher and the tahfizd Al-Qur'an teacher and the homeroom teacher's lack of understanding of Tahfizd Al-Qur'an.